Dependence estimation and visualization in multivariate extremes with applications to financial data - Tailen Hsing; Claudia Klüppelberg; Gabriel Kuhn (Ludwig-Maximilians-Universität München, Sonderforschungsbereich 386 - Statistische Analyse diskreter Strukturen, 2003)
We investigate extreme dependence in a multivariate setting with special emphasis on financial applications. We introduce a new dependence function which allows us to capture the complete extreme dependence structure and present a nonparametric estimation procedure. The new dependence function is compared with existing measures including the spectral measure and other devices measuring extreme dependence. We also apply our method to a financial data set of zero coupon swap rates and estimate the extreme dependence in the data.
urn:nbn:de:bvb:19-epub-1745-2
Keywords: 519; Extreme dependence function; nonparametric estimation; financial data analysis